CORRELATION ACHIEVEMENT MOTIVATION WITH LEARNING ACHIEVEMENT OF STREET CHILDREN IN ELEMENTARY SCHOOL SUBDISTRICT KEMRANJEN DISTRICT OF BANYUMAS - Setiawan, Aji; Suminar, Tri; Sugiyo Pranoto, Yuli Kurniawati (Educational Management, 2020)
Street children who can excel in formal schools can be an example for other street children who prefer to drop out of school. Learning achievements are not only influenced by high intelligence and only capable learning facilities, but learning achievements can also be influenced by other factors such as achievement motivation. The purpose of this research is intended to measure and identify or prove achievement motivation relationship with the learning achievement of street children in District Kemranjen Banyumas District. Penelitian ini dilakukan di kecamatan Kemranjen kabupaten Banyumas dengan 30 anak jalanan sebagai subjek penelitian. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif korelasi dengan menggunakan uji korelasi pearson product moment. The results showed that there was a positive and significant relationship between achievement motivation and learning achievement with a correlation coefficient value of 0.622. The level of relationship between achievement motivated variables with learning achievements has a strong level of relationship with a correlation coefficient value of 0622 * * Located at intervals of 0.60 ? 0799. It is hoped that the study of teachers can have a study that can foster the motivation to achieve their students so that the child can be more in the spirit of learning and achieving their achievements at school.